Peningkatan Kemandirian Finansial Siswa SMK melalui Program Edukasi Kewirausahaan Partisipatif: Optimizing the Potential of Vocational High School Students through Productive Entrepreneurial Activities as an Effort to Achieve Financial Independence - Handayani, Anita; Vilantika, Elok (JURNAL PENGABDIAN MANAJEMEN, 2026)
Global economic developments and increasing competition in the world of work require the younger generation, especially vocational high school (SMK) students, to have financial independence from an early age. Entrepreneurship education at the secondary level is one strategic approach to fostering independence, creativity, and the ability to create business opportunities. This community service activity aims to strengthen practice-based entrepreneurship education through intensive entrepreneurship workshops as an initial intervention in developing productive entrepreneurship among students. The activity was carried out at a private vocational school in Gresik Regency, East Java, involving 50 students from the Production Control Engineering and Industrial Electronics Engineering programs. The methods used included interactive lectures, participatory discussions, and reflection sessions to evaluate students' understanding and follow-up plans. The results of the activity showed a high level of participation, an increase in students' conceptual understanding of entrepreneurship and financial independence, and positive changes in entrepreneurial attitudes and mindsets. Most students are able to identify simple business ideas that are relevant to their skills, although they still require further guidance. This activity is effective as an initial intervention in fostering interest and readiness for entrepreneurship among vocational school students. In the future, a continuous mentoring program is needed to optimize the development of productive businesses and support the achievement of financial independence from school age.